The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1124/jpet.116.232397
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous 5-HT2C Receptors Phosphorylate the cAMP Response Element Binding Protein via Protein Kinase C-Promoted Activation of Extracellular-Regulated Kinases-1/2 in Hypothalamic mHypoA-2/10 Cells

Abstract: Serotonin 5-HT 2C receptors (5-HT 2C R) activate G q proteins and are expressed in the central nervous system (CNS). 5-HT 2C R regulate emotion, feeding, reward, or cognition and may serve as promising drug targets to treat psychiatric disorders or obesity. Owing to technical difficulties in isolating cells from the CNS and the lack of suitable cell lines endogenously expressing 5-HT 2C R, our knowledge about this receptor subtype in native environments is rather limited. The hypothalamic mHypoA-2/10 cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Thus, we investigated here the role of serotonin pathway in promoting PVN TRH expression of dehydrated rats, favoring their anorectic behavior. This is supported by 5HT-induced increase in TRH expression in in vitro systems ( Chen and Ramirez, 1981 ; Shi et al, 1997 ) and by the high expression of 5HT receptors in the PVN ( Marvin et al, 2010 ; Garfield et al, 2014 ; Lauffer et al, 2016 ) that when activated by 5HT injection, induce a reduction of food intake in rodents ( Weiss et al, 1986 ; Leibowitz and Alexander, 1991 ; Bagdy, 1996 ; Woolley et al, 2001 ; Doslikova et al, 2013 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, we investigated here the role of serotonin pathway in promoting PVN TRH expression of dehydrated rats, favoring their anorectic behavior. This is supported by 5HT-induced increase in TRH expression in in vitro systems ( Chen and Ramirez, 1981 ; Shi et al, 1997 ) and by the high expression of 5HT receptors in the PVN ( Marvin et al, 2010 ; Garfield et al, 2014 ; Lauffer et al, 2016 ) that when activated by 5HT injection, induce a reduction of food intake in rodents ( Weiss et al, 1986 ; Leibowitz and Alexander, 1991 ; Bagdy, 1996 ; Woolley et al, 2001 ; Doslikova et al, 2013 ).…”
Section: Discussionmentioning
confidence: 93%
“…For example, 5HT peripheral administration reduces rats’ feeding and the blockade of its effects with antagonists directly injected into the PVN, identifies this hypothalamic nucleus as the key site for controlling its anorectic actions ( Weiss et al, 1986 ; Leibowitz and Alexander, 1991 ). Importantly, there is a high expression of 5HT 1 , 5HT 2 , 5HT 6 receptors in the PVN ( Marvin et al, 2010 ; Garfield et al, 2014 ; Lauffer et al, 2016 ), and the anorectic effects of the serotonergic pathway result by activating 5HT 1 and 5HT 2 receptors ( Bagdy, 1996 ; Doslikova et al, 2013 ), or by the antagonism of 5HT 6 ( Woolley et al, 2001 ). Furthermore, food deprivation-induced hungry animals show reduced 5HT concentration in their brain ( Haleem, 2009 ), whereas those with anorexia present high c-fos expression in different areas including the PVN that is blocked with 5HT antagonists (LPS-induced anorectic rats; Kopf et al, 2010 ), a serotonergic hyperinnervation (anx/anx mice; Jahng et al, 1998 ), or an enhanced 5HT turnover (stress-induced anorectic rats; Reed et al, 2021 ) in the hypothalamus.…”
Section: Introductionmentioning
confidence: 99%
“…mHypoA-2/10 express a wide array of hypothalamic markers [ 38 ]. We have recently reported that these cells behave similar to thyreoliberin -positive neurons of the paraventricular nucleus and that they respond to a wide range of hormones such as melanocortins, serotonin, catecholamines, and IGF [ 20 , 37 , 39 , 40 , 41 ]. GT1-7 cells were kindly provided from Dr. Weiner (University of California, San Francisco, CA, USA) and behave like GnRH-secreting cells of the hypothalamus [ 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, 5-HT 2C R was shown to couple ERK 1/2 via a PLD-and PKC-dependent pathway possibly through Gα 12/13 proteins [14]. The PLD and PKC involvement in ERK 1/2 phosphorylation evoked by 5-HT 2C R stimulation has recently been validated in a mouse hypothalamic cell line [15].…”
Section: Introduction To the 5-ht2cr Protein Structure And Functionmentioning
confidence: 99%